Proportion of mesothelioma attributable to living in industrially contaminated areas in Italy - Roberto Pasetto; Amerigo Zona; Lucia Fazzo; Alessandra Binazzi; Caterina Bruno; Roberta Pirastu; Pietro Comba; Alessandro Marinaccio (Nordic Association of Occupational Safety and Health (NOROSH), 2019)
OBJECTIVES: The aim of this study was to estimate the attributable proportion (AP) of mesothelioma resulting from living in or close to major Italian industrially contaminated areas. METHODS: For populations living close to 39 sites of "national priority for remediation", incident mesothelioma cases were extracted from the Italian National Mesothelioma Registry (ReNaM) in the period 2000‒2011. Each site was classified in one of seven asbestos risk groups (RG) on the basis of the type of industrial plants. RG were ranked by the a priori evidence on asbestos risk. The AP for each RG was calculated as the meta-analytic estimate of AP of sites of the same group by gender and age class (0-64, 65-74, ≥75 years). The sex ratio (men/women) was computed for each RG. RESULTS: Among men, the AP by age class had the same gradient in each RG, with the highest values in the age class 0-64 years and the lowest in the ≥75 class; in the age class 0-64 years, the AP was positive in each RG, >90% in the presence of asbestos cement factories and harbors with shipyards. Among women, the overall AP decreased by RG, with negative values in the last two ranked RG; the AP by age class was variable without a definite gradient. The sex ratio was close to one only in the RG "only asbestos-cement factories"; the highest value (9.6) was observed in the age class 0-64 years in the RG "harbors with shipyard". CONCLUSIONS: The integration of a geographic- and case-based approach provides valuable insights into occupational and environmental determinants of mesothelioma risk in industrially contaminated sites.